2010
DOI: 10.1097/hjh.0b013e32833b49cb
|View full text |Cite
|
Sign up to set email alerts
|

Performance of electrocardiographic criteria for left ventricular hypertrophy as compared with cardiac computed tomography: from the Rule Out Myocardial Infarction Using Computer Assisted Tomography trial

Abstract: Objective Cardiac computed tomography (CT) is a state-of-the-art technology that provides an accurate noninvasive method to quantify left ventricular mass for analysis of left ventricular hypertrophy (LVH). We aimed to examine seven ECG-based LVH criteria against two CT indexation criteria for LVH: a CT-specific body surface area cutoff and the obesity-independent height2.7 criteria. Methods In 333 patients (mean age 53 ± 12 years, 61% men), 64-slice contrast-enhanced CT was performed and 12-lead surface ECG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
4
14
0
Order By: Relevance
“…The sensitivity and specificity was lower in cases with LVMI > 215 g/m 2 than in those with LVMI > 115 g/m 2 . LVH ECG parameters were also verified with computer tomography in the study conducted by Truong et al [20]. The Cornel and Sokolov index achieved 22% and 35% sensitivity and 97% and 90% specificity.…”
Section: Discussionmentioning
confidence: 79%
“…The sensitivity and specificity was lower in cases with LVMI > 215 g/m 2 than in those with LVMI > 115 g/m 2 . LVH ECG parameters were also verified with computer tomography in the study conducted by Truong et al [20]. The Cornel and Sokolov index achieved 22% and 35% sensitivity and 97% and 90% specificity.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, the Cornell voltage and product ECG criteria showed better sensitivity than the Sokolow-Lyon criteria under a fixed specificity of 95%. Most previous studies investigating the performance of different ECG criteria for LVH evaluated by echocardiography or magnetic resonance imaging were conducted in hypertensive patients of the Western countries (21,22). Some studies have shown that there was ethnical difference between hypertensive Whites and African Americans in the ECG diagnostic performance (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, it seems that sex-unspecific dichotomous ECG LVH criteria may produce LVH overdiagnosis in some men and/or underdiagnosis in some women. When left ventricular mass has been estimated with echocardiography or computer tomography, the Cornell-based criteria have shown higher correlation with left ventricular mass than sex-unspecific criteria [7,30].…”
Section: Prevalence and Risk Association Of Various Left Ventricular mentioning
confidence: 98%